Characterization of Minerals Deposit Patimpeng Bone Regency, South Sulawesi through Petrographic. (March 2017) - Putri, I E; Alwi, N D; Subaer,
Abstract: A research on the characterization of minerals from the Patimpeng District Bone Regency, South Sulawesi using petrographic analysis has been conducted. The aims of this study was to identify the minerals deposited in Patimpeng District. Specimens of rocks are grouped into 13 sections. Characterization of samples was conducted in microstructure laboratory, Department of Physics Universitas Negeri Makassar using Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDS) and X-ray Diffraction (XRD). Based on XRD examinations on 13 samples, 9 samples containing albite mineral. The details of XRD analysis, namely; a) PAT_01 containing titanite 16%, albite 65%, hematite 2.9%, periclase 3.4%, and quartz 14%; b) PAT_04 containing thomsonite 18.1%, albite 62%, magnetite 18%, anatase 1.18%, and lime 1.36%; c) PAT_05 containing tetranatrolite 31%, albite 30%, diopside 26%, and magnetite13%; d) PAT_06 containing indialite 8.5%, albite 58%, clinochlore 23%, anatase 5.4%, and magnetite 4.7%; e) PAT_08 containing Thomsonite 42%, albite, 35%, anatase 2.2%, magnetite 7% and magnesium 14%; f) PAT_10 containing Clinochlore 31%, Sodium 5.2%, albite 55%, anatase 3.1%, hematite 1.75%, and magnetite 3.5%; g) PAT_11 containing clinochlore 19.8%, albite 55%, quartz 21.7%, anatase 1.76%, and magnetite 1.9%; h) PAT_12 containg cronstedtite 2, 20%, albite 95.3%, anatase 0.88%, rutile 1, 18% and magnetite 0.4%; i) PAT_13 containing ferrohornblende 5.8%, clinochlore 20.9%, periclase 11.9%, and albite 61%. Sample PAT_12 showed that weight percentage (wt%) of albite was dominant than other minerals. The results of petrographic analysis using X-ray mapping for the sample PAT_12 showed that the entire surface is covered with Si which overlap with Al, Fe, Ca, Na, Mg, and Sb.